2014
DOI: 10.1007/s00221-014-4103-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal disruption of upper-limb anticipatory postural adjustments in cerebellar ataxic patients

Abstract: Voluntary movements induce postural perturbations, which are counteracted by anticipatory postural adjustments (APAs) that preserve body equilibrium. Little is known about the neural structures generating APAs, but several studies suggested a role of sensory-motor areas, basal ganglia, supplementary motor area and thalamus. However, the role of the cerebellum still remains an open question. The aim of this present paper is to shed further light on the role of cerebellum in APAs organization. Thus, APAs that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
4
32
0
Order By: Relevance
“…On the contrary, children with SlowP suffer from a continuous cerebellar degeneration, which conflicts with the consolidation of compensatory functional strategies. This perspective not only fits with the gradual worsening of postural deficits we documented here when passing from healthy children to patients with NonP and to patients with SlowP but would also explain why patients with adult-onset cerebellar lesions show even more pronounced postural deficits [46]. Indeed, neural plasticity gradually but consistently decreases over the lifespan [50].…”
Section: Disease Progression and Postural Behaviorsupporting
confidence: 77%
See 2 more Smart Citations
“…On the contrary, children with SlowP suffer from a continuous cerebellar degeneration, which conflicts with the consolidation of compensatory functional strategies. This perspective not only fits with the gradual worsening of postural deficits we documented here when passing from healthy children to patients with NonP and to patients with SlowP but would also explain why patients with adult-onset cerebellar lesions show even more pronounced postural deficits [46]. Indeed, neural plasticity gradually but consistently decreases over the lifespan [50].…”
Section: Disease Progression and Postural Behaviorsupporting
confidence: 77%
“…This aspect agreed with the general view that assigns to the cerebellum the role of a "timing-machine" [41][42][43][44][45] and leaves the pattern selection to other brain structures, like the basal ganglia. Such a perspective has been confirmed also for what regards APAs in adults [46,47].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, little is known about the precise role of each of these structures in governing APAs. In this regard it has been shown that the cerebellum is involved in APAs timing (Diedrichsen et al, 2005;Bruttini et al, 2015). Moreover, both excitatory and inhibitory APAs are already shaped in the primary motor cortex, M1 (Petersen et al, 2009;Caronni & Cavallari, 2009b).…”
Section: Introductionmentioning
confidence: 98%
“…Cerebellar lesions may selectively impair also the APAs subtending within-limb movements. For instance, in patients with cerebellar ataxia, simple brisk movements of the finger are associated with alterations of the APAs engaging proximal arm muscles (Bruttini et al, 2015; Cavallari et al, 2016). …”
Section: Postural Constraints From Neuroscience To Sports and Rehabilmentioning
confidence: 99%